Epidemiological state-building in interwar Poland: discourses and paper technologies. Issue 1 (24th May 2019) - Kreuder-Sonnen, Katharina
Argument: The paper argues that epidemic surveillance and state-building were closely interconnected in interwar Poland. Starting from the paper technology of weekly epidemiological reporting it discusses how the reporting scheme of Polish epidemics came into being in the context of a typhus epidemic in 1919–20. It then shows how the statistics regarding nation-wide epidemics was put into practice. It is only when we take into account these practices that we can understand the epidemiological order the statistics produced. The preprinted weekly report form registered Jews and Christians separately. Yet, the imagined national epidemiological space that emerged from it hardly took notice of this separation. Rather, the category that differentiated Polish epidemiological space in medical discourse was the capacity of contributing to the state-making practices of epidemic surveillance. This category divided Poland into two regions: a civilized and modern western region and a backward and peripheral eastern region.